Análise de mobilidade no perímetro de Jucurutu - RN: o caso do trecho urbano da RN-118 - Feliciano, Ariandson Neres (Universidade Federal Rural do Semi-Árido, 2019)
The need to understand the nature of commuting and its relationship with urban mobility, transport infrastructure and its consequences on local socioeconomic development is of considerable importance to analyze the reality of inland municipalities that are en route to metropolitan centers. The uncertain nature of urban commuting as a means of transport governs vehicle traffic in cities. However, once the infrastructure demanded by the road modal is not met in order to provide adequate road conditions, a problem of urban mobility is created. This is what happens in the urban limits of Jucurutu, in the state of Rio Grande do Norte, over the urban stretch of RN-118. This case study aimed to evaluate the conditions of urban mobility on the highway that crosses the city limits, to survey the investments and works directed to road transport in the locality, to elaborate a conceptual project of the ideal highway layout in InfraWorks and to compare it with the current state evaluated in the field, pointing out the specific problems, their causes and possible solutions. Given this, it was found that the road requires immediate attention, as it is the backbone of urban mobility in the city.
Artigo
Keywords: Mobilidade Urbana; Infraestrutura; Rodovia; Urban Mobility; Infrastructure; Highway; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA